IMPROVEMENT OF ENDOSCOPIC TECHNOLOGIES IN THE TREATMENT OF POLYPOID NEOPLASMS OF THE GASTROINTESTINAL TRACT (International conference on multidisciplinary science, 2024)
This work is based on the development of a new method for endoscopic removal of superficial polypoid formations of the mucous membrane of the gastrointestinal tract (GIT), which is aimed at reducing the risk of developing specific complications and recurrence of the formation of these formations. The clinical trial was conducted in a retro-prospective format for the period from 2019 to 2023. Endoscopic interventions for upper GIT polyps in the comparison group included cold removal with biopsy forceps – 16 (8.8%) formations, cold loop removal – 26 (14.3%), thermal removal by electroexcision – 94 (51.6%), EMR – 25 (13.7%) cases and dissection in the submucosal layer (ESD) – 21 (11.5%). The introduction of the proposed method of endoscopic removal of polypoid and non-polypoid neoplasms in general allowed to increase the proportion of good immediate and long-term results in excision of polyps of the upper GIT from 73.4% to 95.9%.